Feasibility Analysis of Tilapia Farming in the Maju Bersama Fisheries Group, Central Papua Province - Tebai, Natan; Yoga, Tirta; Nugroho, Anung Prasetyo (Journal of Business Management and Economic Development, 2025)
This study aims to determine the feasibility level of tilapia farming undertaken by the Maju Bersama Fisheries Group in Bomomani Village, Mapia District, Dogiyai Regency, Central Papua Province. The research method employed is a survey approach, using questionnaires and interviews with respondents, namely fish farmers engaged in tilapia farming. This study was conducted over one month, from October to November 2024. The respondents of the study were members of the Maju Bersama Fisheries Group in Bomomani Village, Mapia District, Dogiyai Regency, Central Papua Province. The results show that the fixed costs incurred for cultivating 6,000 tilapia in earthen ponds over one production cycle amount to IDR 10,200,000, variable costs to IDR 10,200,000, and total costs to IDR 37,300,000. Revenue reaches IDR 64,275,000, resulting in a profit of IDR 26,975,000. The Cost Ratio is 1.7, indicating that the tilapia farming business is efficient, as evidenced by an R/C ratio value greater than 1.